1990
DOI: 10.1001/archneur.1990.00530010046017
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic Lateral Sclerosis

Abstract: This chapter was originally intended to cover both amyotrophic lateral sclerosis (ALS) and multiple sclerosis, but we will concentrate on ALS. There are nonetheless several reports from the literature that ionotropic glutamate receptor antagonists have beneficial effects in animal models of multiple sclerosis (1,7,14,58,71,109) and this could develop into a very promising therapeutic area in the future. The interested reader is referred to the following review (59). However, the evidence for involvement of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…However, only in some of them have environmental factors been suggested as a possible explanation for their occurrence [14, 48, 76-82]. This is particularly notable for exposure to metals [48, 77, 80, 81] and to agricultural chemicals [78-81], although exposure to industrial toxins [77] and to paper paste and water treatment plants [82] also appears. As early as 1977, Kilness and Hichberg [76] attributed selenium exposure over a period of 10 years to the small cluster (4 ALS cases that lived within 15 km of each other) that they identified in west-central South Dakota, USA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only in some of them have environmental factors been suggested as a possible explanation for their occurrence [14, 48, 76-82]. This is particularly notable for exposure to metals [48, 77, 80, 81] and to agricultural chemicals [78-81], although exposure to industrial toxins [77] and to paper paste and water treatment plants [82] also appears. As early as 1977, Kilness and Hichberg [76] attributed selenium exposure over a period of 10 years to the small cluster (4 ALS cases that lived within 15 km of each other) that they identified in west-central South Dakota, USA.…”
Section: Discussionmentioning
confidence: 99%
“…As early as 1977, Kilness and Hichberg [76] attributed selenium exposure over a period of 10 years to the small cluster (4 ALS cases that lived within 15 km of each other) that they identified in west-central South Dakota, USA. Almost 30 years ago, Sienko et al [48] detected a cluster in a small fishing village next to Lake Michigan, USA, which is probably associated with a high intake of mercury. In addition to genetics, among the factors to which Sabel et al [80] attribute the existence of 2 significant clusters in south-eastern Finland (one at the time of death and other at the time of birth, of those who died between 1985 and 1995) and another in south-central Finland (at the time of death) is the exposure to heavy metals and agricultural chemicals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All individuals with code 335.2 (motor neuron disease) listed as the underlying or contributing cause of death were considered to have had ALS. In a previous validation study, 17 it was found that ALS was the primary diagnosis listed on death certificates in the majority of instances where code 335.2 was listed as a cause or contributory cause of death. 17 …”
Section: Methodsmentioning
confidence: 99%
“…We requested permission to contact the treating neurologist and for release of relevant medical records from participants who reported a diagnosis of ALS on the open question on major illnesses or on the specific question. Because of the rapidly progressive nature of the disease (median survival 1.5 to 3 years), 1517 many participants with ALS died before we could send the release request for medical records, so the request was sent to the closest family member. After obtaining permission, we asked the treating neurologists to complete a questionnaire to confirm the diagnosis of ALS and to rate the certainty of the diagnosis (definite, probable, or possible) and send medical records.…”
Section: Methodsmentioning
confidence: 99%